Human magnetism in the COVID-19 vaccination era: Rereading of a long-standing scientific fact that has resurfaced - Modjtaba Raoufi; Abdolali Mohagheghzadeh; Shiva Hemmati (Shiraz University of Medical Sciences, 2021)
During vaccination of the COVID-19 pandemic, distributed homemade movies -depicting metal attraction on the body- raised a question in the public mind if ingredients of vaccines play a role in observing this phenomenon. Two primary sources of magnetic fields in the human body are the heart and the brain. The reason for that is coming from a general old rule of physics that electric current creates a magnetic field. Since the heart has a more synchronous depolarization, it can produce a stronger magnetic field around 1 to 14 nT. One possible scenario, which can relate the status in the pandemic era to human magnetism, is the substantial change in the heart's electrical conduction due to infections. The scenario can be supported by frequently related myocardiopathy. The other complementary scenario may be related to the increased amount of paramagnetic substances, such as ferritin, in infected patients and macrophages of the immune system responsible for heme-iron homeostasis. Regarding the presence of biomagnetic materials in higher organisms, the most substantial challenges are the presence of a magneto-sensing protein complex called magnetoreception-related cryptochromes. More detailed investigations are needed to confirm whether the recent observed human magnetism is related to COVID-19 infection and/or vaccination or is just a coincidence. We herein propose to assess the correlation of the electrocardiogram (ECG) and echocardiogram (echo) records when strong human magnetism is observed in clinical trial studies. The relevance of the above-mentioned proteins in drug development is of great value for future pharmaceutical discussions.